Optimasi topologi pada komponen penampan mesin printer 3dimensi dengan metode generative desain - Utama, D.W. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2017)
The process of developing a product is currently demanded faster implementation, where the use of CAD can help speed up the process of product development. The commonly CAD software used is parametric method software, where the user can change the shape of the model by changing the parameters accordingly, after which, the model can be directly analyzed using finite element analysis method. If the design is needed to be changed, then the designer should change the parameters in  CAD module and then performed FEA analysis again. This process is often done repeatedly to produce a product model that meets the needs and criteria specified. Generative design method is a method that uses a series of design criteria and design limitations. In this paper the generative design method is a feature in CAD where topology optimization is applied in creating the design of the tray table. The tray table is the main component of the 3D printer that has design criteria such as static load of 17.912N and geometric boundaries. The generative design used to optimize the weight of the component is reshaped again according to the criteria and aesthetics of the form. The CAD model is retested with the FEA method to ensure safe design. The results show that the best optimazation is at 55% weight reduction with the von mises stress 2.12 MPa and the deflection about 0.129mm.